The impact of chronic depression on acute and long-term outcomes in a randomized trial comparing selective serotonin reuptake inhibitor monotherapy versus each of 2 different antidepressant medication combinations - Sung, Sharon C.; Haley, Charlotte L.; Wisniewski, Stephen R.; Fava, Maurizio; Nierenberg, Andrew A.; Warden, Diane; Morris, David W.; Kurian, Benji T.; Trivedi, Madhukar H.; Rush, A. John (The Journal of Clinical Psychiatry, 2012)
Objective: To compare sociodemographic and clinical features, acute and continuation treatment outcomes, and adverse events/side effect burden between outpatients with chronic (current episode > 2 years) versus nonchronic major depressive disorder (MDD) who were treated with combination antidepressant therapy or selective serotonin reuptake inhibitor (SSRI) monotherapy. Method: 663 outpatients with chronic (n = 368) or nonchronic (n = 295) moderate to severe DSM-IV-TR MDD (17-item Hamilton Depression Rating Scale score ≥ 16) were enrolled from March 2008 through September 2009 in a single-blind 7-month prospective randomized trial conducted at 6 primary and 9 psychiatric care sites across the United States. Participants were treated with escitalopram monotherapy plus placebo or 1 of 2 combination treatments (bupropion sustained-release [SR] + escitalopram or venlafaxine extended-release [XR] + mirtazapine). Analyses compared baseline sociodemographic and clinical characteristics, rates of remission (at least 1 of the last 2 consecutive scores on the 16-item Quick Inventory of Depressive Symptomatology-Self-Report [QIDS-SR₁₆] < 6, with the other < 8), and adverse events/side effect burden (Frequency, Intensity, and Burden of Side Effects Ratings) obtained at 12 and 28 weeks. Results: Participants with chronic MDD were at greater socioeconomic disadvantage and had greater medical and psychiatric disease burden. The chronic and nonchronic groups did not differ in rates of remission at 12 weeks (35.9% vs 42.0%, respectively; odds ratio [OR] = 0.778, P = .1500; adjusted OR [AOR] = 0.956, P = .8130) or at 28 weeks (41.0% vs 49.8%, respectively; OR = 0.706, P = .0416; AOR = 0.837, P = .3448). Participants with chronic MDD had higher final QIDS-SR₁₆ scores and smaller overall percent changes in QIDS-SR₁₆ from baseline to exit, but these differences did not remain after adjusting for covariates. There were no significant differences in adverse events or side effect burden. No significant interactions were found between chronicity and type of treatment at 12 or 28 weeks. Conclusion: Chronicity of illness does not appear to differentially impact acute or longer-term outcomes with SSRI monotherapy or combination antidepressant medication treatment in patients with moderate to severe nonpsychotic MDD. (PsycInfo Database Record (c) 2020 APA, all rights reserved)
Keywords: Adolescent; Adult; Aged; Antidepressant Drugs; Antidepressive Agents; Bupropion; Chronic Disease; Chronicity (Disorders); Citalopram; Comorbidity; Cyclohexanols; Delayed-Action Preparations; Demographic Characteristics; Depressive Disorder, Major; Drug Therapy; Drug Therapy, Combination; Female; Humans; Major Depression; Male; Mianserin; Middle Aged; Personality Inventory; Prognosis; Prospective Studies; Psychometrics; Serotonin Reuptake Inhibitors; Serotonin Uptake Inhibitors; Side Effects (Drug); Single-Blind Method; Treatment Outcome; Treatment Outcomes; Venlafaxine Hydrochloride; Young Adult; acute & long-term outcomes; chronic depression; clinical features; combination antidepressant therapy; drug side effects; selective serotonin reuptake inhibitor monotherapy; sociodemographic features